조선 CIM을 위한 제품 모델의 간명한 표현법 - 윤덕영(D. Y. Yoon); 조학종(H. J. Jo); 허흥원(H. W. Suh); 김기언(K. E. Kim); 고영화(Y. H. Ko); 이원준(W. J. Lee); 김훈주(H. J. Kim); 임화규(H. G. Lim); 우일국(I. K. Woo); 송치봉(C. B. Song) (大韓造船學會 論文集, 1994)
The purpose of CIM for shipbuilding should be focused on the efficient processing of information among design, process planning and scheduling activities. The most essential technology for shipbuilding CIM is the product model. This model should not only define a physical product "ship" but also a process "ship production". Major activity for ship production is assembly, which requires intensive use of the relationships among parts of ship structure. Other production information are painting area. shape. weight, etc. The fact that major ship structure is "stiffened-plate" type, which allows us to handle the plate thickness as non-geometric information for practical purpose. Therefore. the geometric model for ship product model should handle the relationship among parts(so called topology) efficiently. We find that a face oriented non manifold data structure can meet this requirement. We apply this non-manifold data structure to the ship compartmentation, structural design, and assembly. 조선 CIM 시스템은 제품 모델을 중심으로 한 정보의 통합화를 중점적으로 추구하여야 하므로, 이 제품 모델을 기능 모델과 형상 모델로 구분하였다. 조선을 위한 제품 모델의 근간이 되는 형상 모델을 오일러 조작을 기초로 하는 비다양체 모델의 자료 구조를 이용하여 각각 구획 배치, 구조 설계 및 공정 계획의 입장에서 이용하는 방법에 대하여 연구하였다.